Prototype of automatic switching off and on of public lighting for the city of Pampas in the province of Tayacaja in the Huancavelica region - Bernardo Osores , Gabriela Dayana (2022)
The purpose of this article is the design and implementation of an automation prototype for public lighting systems; Likewise, a model is built to test the functioning of the implemented prototype, simulating the provision of public lighting service automatically. In the prototype implementation, the Arduino board, LDR sensor and LED diodes were used; The monitoring graphical interface was developed in the block-based language mBlock, due to its friendly language characteristics to develop interfaces in a simple way, without the need for advanced knowledge of programming languages. The methodology used in the development of the prototype is based on 4 phases: understanding the problem, plan of activities, execution of activities and testing or evaluation of the solution. This work was developed in the Information Management course with students of the II cycle of the industrial engineering.